الاختیار الامثل لالوان غرفة الطفل وفق بعض المتغیرات (Journal of the College of Education for Women, 2019)
Color is perhaps the most important element in art because it is what first attractsattention when looking at any thing or any work of art.the important of colors is clear inthe life of every one of the people. A good color scheme in all aspect s of life is a clearindication of a highly developed society and nation. It also has appositive effect on theindividual s by providing feeling s of joy and comfort – such feeling encourage hard workand productivity whether at home. At school or at work.A study of childhood and attention of the criteria by which to measure the progressof society and its development as the interest in childhood is in fact interesting Bmstqublathe whole nation. The current research sheds light on the importance of colors and theirrole in the lives of children and variables that reflected on their behavior and their actionsin life. The importance of the subject.The researcher chose to kindergarten aged children (4-6 years), which formed inthe this stage, the first seed of the aesthetic taste and understanding of what the resentmentof the size and color of the children. And the tendency of the child in this age to use thecolors of the design and choice of colors, favorite games has. Therefore, parents must takeinto account the environment variable and gender when choosing a favorite color ofAlatvalhm.